2001
DOI: 10.1076/ejom.39.5.277.7380
|View full text |Cite
|
Sign up to set email alerts
|

The Ultrastructure of Primary Cilia in the Endocrine and Excretory Duct Cells of the Pancreas of Mice and Rats

Abstract: A primary cilium was frequently observed in the endocrine alpha, beta and delta cells, as well as in the excretory duct cells of the pancreas of normal mice and rats. The characteristic components of the cilium including the basal body, axoneme (shaft), and terminal part were clearly recognizable. The basal body or distal centriole surrounded by Golgi vesicles was perpendicularly oriented to the proximal centriole, and a dense striated band was seen filling the gap between them. The microtubules of the basal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…Therefore, an interesting inquiry to be addressed in future studies is whether BBS patients and BBS protein-knockout mice normally express SSTR3 on the primary cilia of insulin cells. Cells of pancreatic ducts and islets possess the primary cilia, but acinar cells of the exocrine pancreas apparently lack them (1,5,22,39). An electron microscopic study by Yamamoto and Kataoka (39) has reported in detail the ultrastructure of primary cilia on islet cells of some animal species.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an interesting inquiry to be addressed in future studies is whether BBS patients and BBS protein-knockout mice normally express SSTR3 on the primary cilia of insulin cells. Cells of pancreatic ducts and islets possess the primary cilia, but acinar cells of the exocrine pancreas apparently lack them (1,5,22,39). An electron microscopic study by Yamamoto and Kataoka (39) has reported in detail the ultrastructure of primary cilia on islet cells of some animal species.…”
Section: Discussionmentioning
confidence: 99%
“…This is attributed, at least in part, to a reduction in the expression of Dync2li1 and Ift88, two RFX3 target genes coding for proteins implicated in IFT. The function of primary cilia found on islet cells is unknown (33). However, there is growing evidence that primary cilia function as sensory organelles that relay signals affecting the development and physiological responses of the cells that carry them.…”
Section: Discussionmentioning
confidence: 99%
“…Islet cells carry primary cilia (33). We examined these cilia in Rfx3 ϩ/ϩ and Rfx3 Ϫ/Ϫ dpc 19 embryos by staining pancreas sections with antibodies against cilia-specific tubulin isoforms (Fig.…”
Section: Cilia Are Defective On Islet Cells Of Rfx3mentioning
confidence: 99%
“…Overall, the distribution of cilia correlates nicely with the bgalactosidase staining described above (see Figure 3) and with published data. 76 Previously, it was demonstrated that cilia were severely stunted in the collecting duct epithelium of the kidney and the ependymal cells lining the ventricles in the brain of Tg737 orpk mutant. 58,77 To determine if similar events were occurring in the duct and islet cells in the pancreas, we analyzed sections of the mutant pancreas for defects in the cilia by immunofluorescence (Figure 7a-d, right panels).…”
Section: Presence Of Cilia In the Pancreas And Cilia Defects In Tg737mentioning
confidence: 99%